Formae speciales of cereal powdery mildew: close or distant relatives?. (6th January 2014) - Troch, Veronique; Audenaert, Kris; Wyand, Rebecca A.; Haesaert, Geert; Höfte, Monica; Brown, James K. M.
Summary Powdery mildew is an important disease of cereals, affecting both grain yield and end‐use quality. The causal agent of powdery mildew on cereals, Blumeria graminis, has been classified into eight formae speciales (ff.spp.), infecting crops and wild grasses. Advances in research on host specificity and resistance, and on pathogen phylogeny and origins, have brought aspects of the subspecific classification system of B. graminis into ff.spp. into question, because it is based on adaptation to certain hosts rather than strict host specialization. Cereals therefore cannot be considered as typical non‐hosts to non‐adapted ff.spp. We introduce the term 'non‐adapted resistance' of cereals to inappropriate ff.spp. of B. graminis, which involves both pathogen‐associated molecular pattern‐triggered immunity (PTI) and effector‐triggered immunity (ETI). There is no clear distinction between the mechanisms of resistance to adapted and non‐adapted ff.spp. Molecular evolutionary data suggest that the taxonomic grouping of B. graminis into different ff.spp. is not consistent with the phylogeny of the fungus. Imprecise estimates of mutation rates and the lack of genetic variation in introduced populations may explain the uncertainty with regard to divergence times, in the Miocene or Holocene epochs, of ff.spp. of B. graminis which infect cereal crop species. We propose that most evidence favours divergence in the Holocene, during the course of early agriculture. We also propose that the forma specialis concept should be retained for B. graminis pathogenic on cultivated cereals to include clades of the fungus which are strongly specialized to these hosts, i.e. ff.spp. hordei, secalis and tritici, as well as avenae from cultivated A. sativa, and that the forma specialis concept should no longer be applied to B. graminis from most wild grasses.